Exploração do trabalho escravo rural no Brasil, a função social da propriedade e os principais mecanismos jurídicos de combate à escravidão contemporânea - Teódulo , Cristiana Araújo (2015)
This dissertation uses the deductive method, relying on a qualitative survey, conducted from a bibliographic review of the legal literature available on the subject and from documents obtained in civil investigations and public civil actions, in charge of the prosecution of Job. Therefore, the purpose of this dissertation is the study of labor analogous to slavery in rural Brazil of the XXI century. The work has, scope, analyze the definition, characterization and tools currently used to combat this legal, social and economic phenomenon. The main obstacles to the eradication of labor analogous to contemporary slave are the absence of an objective concept of the phenomenon and the difficulty of its characterization and delineation. Thus, the research demand, despite the controversial doctrinal and jurisprudential divergence, defining labor analogous to slave and indicate their main ways to collaborate to its extinction. In line with Art. 149 of the Penal Code, as amended by Law No. 10,803 / 2003, the concept of labor analogous to slavery is broader than the concept of forced labor conceived by the International Labour Organization, comprising both forced labor as degrading, since the main basis for the sealing of all contemporary forms of slavery stems from the principle of human dignity. The concept of labor analogous to slavery, which was given by the criminal law, even received praise from the OAS and the ILO because it is very current. It follows from the fact that the courts are already using the aforementioned legal provision to prosecute such crimes, although the present legal mechanisms to combat contemporary forms of slavery are not efficient to solve the problem. The fact, however, is that the whiplash issue does not fall within just the legal harvest, labor or criminal, since it also covers economic and social orders. Therefore, the study now undertaken ensure the use of land expropriation as an effective means intended to abolish any kind of work analogous to rural slave, a fact that stems from two reasons: A priori, for it means a relevant insertion mechanism agrarian reform, and a posteriori, because the land expropriation, forced upon those who fall within the criminal type, is a feather in the rural property owner who, disregarding the social, explores the work analogous to slavery.